Water-extractable organic matter linked to soil physico-chemistry and microbiology at the regional scale. (May 2015) - Guigue, J.; Lévêque, J.; Mathieu, O.; Schmitt-Kopplin, P.; Lucio, M.; Arrouays, D.; Jolivet, C.; Dequiedt, S.; Chemidlin Prévost-Bouré, N.; Ranjard, L.
Abstract: A better understanding of the links between dissolved organic matter and biogeochemical processes in soil could help in evaluating global soil dynamics. To assess the effects of land cover and parental material on soil biogeochemistry, we studied 120 soil samples collected from various ecosystems in Burgundy, France. The potential solubility and aromaticity of dissolved organic matter was characterised by pressurised hot-water extraction of organic carbon (PH-WEOC). Soil physico-chemical characteristics (pH, texture, soil carbon and nitrogen) were measured, as was the δ 13 C signature both in soils and in PH-WEOC. We also determined bacterial and fungal abundance and the genetic structure of bacterial communities. Our results show that the potential solubility of soil organic carbon is correlated to carbon and clay content in the soil. The aromaticity of PH-WEOC and its δ 13 C signature reflect differences in the decomposition pathways of soil organic matter and in the production of water-extractable organic compounds, in relation to land cover. The genetic structure of bacterial communities is related to soil texture and pH, and to PH-WEOC, revealing that water-extractable organic matter is closely related to the dynamics of bacterial communities. This comprehensive study, at the regional scale, thus provides better definition of the relationships between water-extractable organic matter and soil biogeochemical properties. Highlights: An integrated study of WEOM at the regional scale. We report the effect of land cover and parental material on soil biogeochemistry. Soil C and clay contents determine the solubility of soil organic matter. Soluble organic matter characteristics related to microbial communities.